Hypophyso-gonadal response to GnRH pulsatile infusion at high altitude - Castillo, Óscar (2011)
Introduction: It is known that fertility of normal high altitude dwellers is similar to that at sea level. Objectives: To determine the hypophyso- gonadal reserve using a pulsatile methodology with low doses of GnRH. Design: Experimental, basic study. Setting: Instituto de Investigaciones Clinicas, Universidad Nacional Mayor de San Marcos, Lima, and Laboratorio de Ciencias Biologicas, Universidad San Antonio Abad, Cusco, Peru. Participants: Sea level and high altitude normal subjects. Interventions: Twelve normal male high altitude dwellers (Cusco, 3395 m.a.s.l.) and 12 subjects living at sea level (Lima, 150 m.a.s.l.) were submitted to an intermittent intravenous infusion of GnRH for 24 hours. Serum LH, FSH and testosterone concentrations were measured using RIA techniques. Main outcome measures: LH, FSH y testosterone concentrations. Results: LH, FSH and testosterone basal concentrations were similar in both groups. Significant LH increases from basal concentrations was observed from 3 to 24 hours in both groups. Conclusions: Although no significant differences in serum FSH and testosterone mean concentrations were found during infusion to both groups, only high altitude dwellers presented significant FSH elevation from their basal values which might suggest that the normal high altitude dwellers have a higher hypophysis reserve.